Penggunaan Fasilitas WiFi dan Pengaruhnya terhadap Indeks Prestasi Mahasiswa Prodi Pendidikan Matematika (Studi pada Mahasiswa Prodi Pendidikan Matematika STAIN Zawiyah Cot Kala Langsa) - Jelita, Jelita (IAIN PADANGSIDIMPUAN, 2013)
ABSTRACTThe position of information technology is important in all aspects of life. One of the developments that are rapidly from information technology becomes a trending topicPenggunaan Fasilitas Wifi...........Jelita 120is free Wi-Fi. In the world of lectures, students are the biggest consumer that uses